2020
DOI: 10.4081/br.2020.30
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer anti-hormonal therapy and rheumatic diseases: linking the clinical to molecular world

Abstract: Anti-hormonal therapies are used in the treatment of hormone dependent breast cancer. Their use may be complicated with the onset of arthralgia and autoimmune diseases. Recently a clinical relationship between oestrogen, anti-oestrogen therapy and rheumatic diseases has been reported in the literature, but, until now, experimental supporting data about the interacting biochemical pathways involved are still very limited. The understanding of this molecular link may provide important information to elucidate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…As suggested also by Melillo et al [169], in a recent review on the possible molecular mechanisms responsible for the onset of autoimmunity during AIs therapy, other biological pathways may involve IL-17. In a genome-wide association study, a SNP signal on chromosome 14 that mapped near the 3' end of the T-cell leukemia 1A (TCL1A) gene, was identified as being associated with musculoskeletal pain in women in adjuvant AIs therapy for BC.…”
Section: Etiopathophysiology Of Ais-induced Rheumatic Autoimmune Disementioning
confidence: 66%
See 1 more Smart Citation
“…As suggested also by Melillo et al [169], in a recent review on the possible molecular mechanisms responsible for the onset of autoimmunity during AIs therapy, other biological pathways may involve IL-17. In a genome-wide association study, a SNP signal on chromosome 14 that mapped near the 3' end of the T-cell leukemia 1A (TCL1A) gene, was identified as being associated with musculoskeletal pain in women in adjuvant AIs therapy for BC.…”
Section: Etiopathophysiology Of Ais-induced Rheumatic Autoimmune Disementioning
confidence: 66%
“…In this context, IL-17 acts as a key amplifier of the inflammatory response, as it initiates the synthesis of several other inflammatory mediators, such as granulocyte-macrophage colony stimulating factor, Prostaglandin (PG)-E2 and IL-8, which, in turn, increase the inflammatory cascade [171]. The estradiol-dependent regulation of this cytokine and of its receptor expression, mediated by TCL1A, might help to explain the association of TCL1A with musculoskeletal symptoms, within the range of SpA described in patients treated with AIs [127,169]. Other pro-inflammatory cytokines, such as TNF-α and IL-1β, are known for their central role in the pathogenesis of autoimmune diseases, and previous evidence showed that estrogens modulated their release, controlling the expression of CD16 receptor on monocytes and macrophages [172].…”
Section: Etiopathophysiology Of Ais-induced Rheumatic Autoimmune Disementioning
confidence: 99%